ECONOMETRIC RESEARCH OF PERSPECTIVES OF THE DEVELOPMENT OF THE JAPANESE ECONOMY - D. Shevchenko (Вестник университета, 2017)
In the article, the analysis of modern aspects of development of the Japanese economy, in particular dynamics of such indicator as a gross domestic product is carried out. The Japanese model of attraction of direct foreign investments and its features are considered. An empirical study of the influence of factors on the knowledge-intensive sector of Japan using a model with fixed and individual effects was also conducted. As a result, the conclusion was made about the importance of foreign direct investment and self-financing within the framework of the forecast of the knowledge-intensive sector of Japanese economy.